Pengaruh Metode Pembelajaran dan Kecerdasan Interpersonal Terhadap Hasil Belajar Sejarah Siswa SMA - Myristica Imanita (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2014)
Abstract This study aimed to determine the effect of learning methods and student’s intrepersonal intelligence on the outcome of history learning on the students. This research is quantitative research using design treatment by level 2x2 The research date was taken from the observation, tests and questionnaires. The results showedthat(1) history learning outcome of students who follow STAD instructional methods higher than students whofollow conventional linstructional methods, (2) there is interaction effect between instructional methods and interpersonal intelligence on history learning outcome of students, (3) history learning outcomesof studentswhofollow STAD instructionalmethodwithhighinterpersonalintelligence, higher thanstudents who followconventional linstructionalmethod, (4)historylearning outcomesof studentswhofollow STAD instuctionalmethodswithlowinterpersonalintelligence, lower thanstudents who followconventional instructional methods Keywords : History learning outcome, instructional method, interpersonal intelligence